2021
DOI: 10.1177/09732179211060613
|View full text |Cite
|
Sign up to set email alerts
|

Rooming in and Breast Feeding Practices and Rate of Horizontal Transmission of SARS-CoV-2 Virus in 5 UAE Hospitals—An Observational Study

Abstract: Objectives: To assess risks of mother to child horizontal transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus during rooming in and breastfeeding in infants born to mothers with the coronavirus (COVID-19) disease. Design: Retrospective observational study. Participants: Five tertiary care centers located in the United Arab Emirates. Infants born to mothers positive for SARS-CoV-2 polymerase chain reaction (PCR) at the time of delivery, born between April 1 and October 30, 2020. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, C-reactive protein and D-dimer levels were significantly higher in pregnant patients ( Hazari et al, 2021 ). Fortunately, two studies have shown a minimal risk of vertical transmission as well as symptomatic infection of COVID-19 in neonates born to infected mothers ( Hazari et al, 2021 ; Kaushal et al, 2021 ). In Qatar, two cases of infected pregnant women, one in her 26th week and one in her 32th week of gestation, were reported.…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
“…Furthermore, C-reactive protein and D-dimer levels were significantly higher in pregnant patients ( Hazari et al, 2021 ). Fortunately, two studies have shown a minimal risk of vertical transmission as well as symptomatic infection of COVID-19 in neonates born to infected mothers ( Hazari et al, 2021 ; Kaushal et al, 2021 ). In Qatar, two cases of infected pregnant women, one in her 26th week and one in her 32th week of gestation, were reported.…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%